Blues of Heaven, The : Poems - Ras, Barbara (Book collections on Project MUSE., 2021)
"In The Blues of Heaven, Barbara Ras delivers her characteristic subjects with new daring that both rattles and beguiles. Here are poems of grief over her brother's death; doors to an idiosyncratic working-class childhood among Polish immigrants; laments for nature and politics out of kilter. Ras portrays the climate crisis, guns out of control, the reckless injustice and ignorance of the United States government. At the same time, her poems nimbly focus on particulars-these facts, these consequences-bringing the wreckage of unfathomable harm home with immediacy and integrity. Though her subjects may be dire, Ras also weaves her wise humor throughout, moving deftly from sardonic to whimsical to create an expansive, ardent, and memorable book."--Publisher's description.